PERENCANAAN PENDIDIKAN KARAKTER DALAM PERKULIAHAN MATEMATIKA EKONOMI DAN BISNIS DI PROGRAM STUDI D3 AKUNTASI UNIVERSITAS PAMULANG - Indah Pertiwi (Universitas Pamulang, 2018)
AbstractCharacter is the essence of every human life. The character of a mature person will have an impact on the preparation of a mature self that is ready to deal with all the challenges and conflicts in life. Character can be developed one of them through education from early childhood to college level. All universities in Indonesia carry out the government's mission to develop character education as a continuation of the development of character education in schools, as well as at Pamulang University. Character education should be planned by formulating in the curriculum, applying it with educational methods, and practiced in the learning process. Economics and Business Mathematics course in D3 Accounting Study Program is also required to be able to integrate character education in the learning process. The planning can be done include: (1) Developing Semester Learning Plan (RPS) is characterized by character education; (2) Assess CPL to determine the character values to be developed; (3) Developing character education model based on character education in Economics and Business Mathematics; (4) Develop active lectures / activities that enable students to have opportunities to internalize values and demonstrate them in appropriate behaviors; (5) Designing tasks that enable students to develop character values; and (6) Designing lecturing evaluations covering cognitive, affective and psychomotor aspects. Keywords: character education, economic and business mathematics, planning